Female alpine racers lived experiences of anterior cruciate ligament injury and return to skiing - Doyle-Baker, P.; Collins, E.; Lawrence, K. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Anterior Cruciate Ligament (ACL) injury occurs frequently in the sport of alpine ski racing comprising approximately 25% of all injuries. Female racers are 2 to 8 times more likely than males to rupture their ACL and often do not return to sport as quickly or with as much success as their male counterparts. Therefore, the purpose of this study was to explore the lived experience of ski racers who sustained an ACL inJury and how these experiences were meaningful to their return to sport. The study used qualitative research methods and concepts of Hermeneutic Phenomenology to provide descriptions of these experiences.